Dampak Kebijakan Efisiensi Anggaran pada Kantor Wilayah Direktorat Jenderal Perbendaharaan Provinsi Sulawesi Tengah: Implikasi Terhadap Belanja Pemerintah - Ni Luh Dian Sundari Indah; Rahma Masdar; Masruddin Masruddin; Muhammad Ikbal Abdullah; Jamaluddin Jamaluddin (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The budget efficiency policy implemented by the government through Presidential Instruction Number 1 of 2025 has brought about changes in budget management for ministries and agencies, including at the Regional Office of the Directorate General of Treasury for Central Sulawesi Province. This study aims to analyze the impact of budget efficiency policies on the composition of government expenditure including personnel expenditure, expenditure on goods, and capital expenditure and to examine their application to budget management. The study employs a descriptive qualitative approach, utilizing primary data obtained through interviews with the Head of the Finance Sub-division and secondary data consisting of budget documents, budget realization reports, and relevant regulations. Data were collected through observation, interviews, and documentation, and subsequently analyzed using data reduction, data presentation, and conclusion-drawing techniques. Research findings indicate that the efficiency policy does not curtail employees' rights but rather drives adjustments to honoraria and the adoption of digital-based work patterns. The most significant impact was on expenditure for goods achieved through reductions in official travel, in-person meetings, meeting refreshments, and other operational needs while capital expenditure was prioritized for strengthening digital infrastructure and information technology. Overall, the efficiency policy fosters the management of government spending that is more effective, adaptive, and oriented towards resource optimization, without disrupting the execution of the organization's duties and functions.